TRANSFER PRICING, KOMPENSASI RUGI FISKAL, FINANCIAL DISTRESS, KONEKSI POLITIK DAN KEPEMILIKAN INSTITUSIONAL TERHADAP AGRESIVITAS PAJAK - Dennes Catur Sagita; Mirna Dyah Praptitorini (PERFORMANCE: Jurnal Bisnis & Akuntansi, 2025)
This study aims to determine the effect of transfer pricing, fiscal loss compensation, financial distress, political connections and institutional ownership on tax aggressiveness. The data used in this study are quantitative and secondary data obtained from the company's annual report using purposive sampling technique. The population in this study used 66 energy sector companies listed on the Indonesia Stock Exchange (IDX) in 2019-2023. Data analysis in this study used multiple linear regression with SPSS 27. The results showed that the transfer pricing, political connection and institutional ownership variable had no effect on tax aggressiveness, while the fiscal loss compensation variable and financial distress had a positive influence on tax aggressiveness.